The Emergency Medical Treatment and Active Labor Act - Maneesha Sakhuja; Caleb Ward; Vanessa Madrigal; Joseph Shapiro (Pediatric Emergency Care, 2026)
The Emergency Medical Treatment and Active Labor Act (EMTALA), enacted in 1986, established the legal foundation for access to emergency medical care in the United States. This review examines EMTALA’s historical origins, core requirements, and implications for pediatric emergency practice. The law emerged in response to widespread patient dumping practices in the 1980s, when hospitals routinely transferred or refused care to uninsured patients. In the 4 decades since, amendments and regulatory clarifications have expanded the law’s scope and strengthened enforcement mechanisms. The modern iteration of EMTALA imposes 3 fundamental obligations on Medicare-participating hospitals with dedicated emergency departments: providing an appropriate medical screening examination, stabilizing emergency medical conditions, and facilitating appropriate transfers when necessary. Pediatric-specific considerations include the “reverse dumping” provision, which requires hospitals with specialized pediatric capabilities to accept appropriate transfers when capacity exists, and standards for pediatric transport during interfacility transfers. While EMTALA provides critical protections, its narrow focus on emergency care raises ethical questions about whether this minimal standard adequately meets broader child health needs. Understanding EMTALA’s requirements and limitations is essential for pediatric emergency providers navigating both clinical and legal obligations in contemporary practice.